Planejamento estratégico participativo na gestão de uma escola estadual paulista - Ponchio, Raquel (2014)
The school management is one of the areas of professional practice of education responsible for the operation and coordination of all dimensions and actions of educational work. To ensure high standards of teaching and effective community participation, as from the use of methods that create conditions of autonomy, integration, dynamism and mobilization of human and material resources for the overall success of the school. The objective of this study is to propose contributions to a participatory strategic planning model in a school unit of state s network This is a descriptive study, conducted by the method of case study with 76 social subjects, divided into three categories of analysis being: I Teachers and general staff;II-members of the student body; III- Members of the parent-teacher association. The results show that the main forces of the school include: (a) teacher motivation, (b) professional ethics, (c) teachers training. The main weaknesses are :(a) school leadership, (b) participatory management, (c) disruption of students. The opportunities are: (a) development index of the state of São Paulo, (b) economic situation of the country, (c) partnerships with the 2nd sector. The threats are: (a) social violence, (b) deficiency in the evaluation of school administrators, (c) economic situation the country. The conclusion is that the school has a low performance in fulfilling its duties requiring a strategic plan that aims to achieve the goals of education, the principles of democratic management associated with the effectiveness of promoting learning oriented training and educational activities of the students.